Multimodal input in second-language speech processing. (April 2021) - Hardison, Debra M.
Abstract : This timeline provides an update on research since 2009 involving auditory-visual (AV) input in spoken language processing (see Hardison, 2010 for an earlier timeline on this topic). A brief background is presented here as a foundation for the more recent studies of speech as a multimodal phenomenon (e.g., Rosenblum, 2005).